Text Messaging and English Writing Proficiency of Grade Six Pupils - Biray, Ersyl T.; Dalisay, Ma. Teresa A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This descriptive correlation study determined the influence of text messaging to the English writing proficiency of Grade Six pupils in Nagustan Elementary School in the District of Nabas, Aklan, Philippines during the School Year 2019 - 2020. Data about the participants’ profile and frequency of text messaging were gathered using a survey questionnaire to 41 Grade VI pupils. Results showed that majority of the pupils have Very Satisfactory grades in English during the 3rd grading period. A greater number of the pupils spend 2 to 3 hours in text messaging while only few spend less than 1 to 2 hours. Generally, the pupil participants have outstanding English writing performances in sentence structure, idea development, and understanding of literature/texts, and very satisfactory in organizational pattern, text support, transitional devices, word choice, and language mechanics. Only a few of them have satisfactory performance and a lesser number needs improvement in all criteria. A very high positive relationship was found between the grade in English and frequency of text messaging to the English writing proficiency of the participants. This implies that the higher the grade of a pupil in English and the more frequent they engage in text messaging, the more proficient they are in writing.